Zaburzenia glacitektoniczne w rejonie Dychów - Nowogród Bobrzański = Glacitectonics dislocation of Dychów- Nowogród Bobrzański area - Kraiński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents detailed description of geological structure of Dychów canal subsoil based on archive data. The continuity of glacitectonical disturbances from Wał Zielonogórski was proved. This disturbances occurs under younger, not disturbed sediments.
Keywords: Wał Zielonogórski; zaburzenia glacitektoniczne; Bóbr; glacitectonical di sturbances